Tuberculosis in Takayasu arteritis: a retrospective study in 1105 Chinese patients - Zhang, Ying (J Geriatr Cardiol, 2019)
BACKGROUND: Tuberculosis (TB) infection has been reported to have a possible relationship with the occurrence and clinical course of Takayasu arteritis (TA). We aimed to describe the characteristics of TB in a large population of TA patients. METHODS: We included a total of 1105 patients with TA, who were hospitalized between January 1992 and December 2017. Comparisons of clinical features were made according to the presence of TB. RESULTS: Among the 1105 patients, 109 (9.9%) had TB, including 53 patients (48.6%) diagnosed with TB before the onset of TA, 23 (21.1%) with a concurrent diagnosis of TB and TA, and 24 patients (22.0%) who developed TB after TA. Pulmonary TB was the most frequently identified (97 patients, 89.0%). Patients with TB had more frequent involvement of the pulmonary artery and experienced more chest discomfort and constitutional symptoms but had less interventional treatment. Demographic characteristics, comorbid diseases, and use of steroids were similar between patients with and without TB. CONCLUSIONS: The proportion of Chinese TA patients with TB was not low, and about half of the patients had TB before TA. Pulmonary TB was the most common. Pulmonary artery involvement and pulmonary hypertension was more frequent in TA patients with TB.